Physiological And Psychological Verbs In Behavioral Process: A Systemic Functional Grammar Approach - Fuji Alamsari (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2018)
The aim of this study is to analyze the English Verbs in Behavioral Processes using a Functional Grammar Approach. The object of this study is Behavioral processes. Then, the purpose of this study is to analyze the English verbs in behavioral process which are classified physiological and psychological verbs. The, the researcher found the meaning of the verbs using physiological and psychological terms. The method of this study is descriptive. The writer has classified physiological verbs which are physiological and psychological verbs of behavioral process. The result based on data of physiological verbs in behavioral process are take a deep breath, clear throat, smell, listen to, watch, notice, look and snif . In addition to, the psychological verbs of behavioral process are give a short laugh, cry out, gaze, smile, laugh, groan, fear and growl.